2016
DOI: 10.1093/jxb/erw367
|View full text |Cite
|
Sign up to set email alerts
|

A flow cytometric method for estimating S-phase duration in plants

Abstract: HighlightWe estimated S-phase duration for several plant species by following EdU-labeled nuclei from G1 to G2 using bivariate flow cytometry. S-phase duration is relatively consistent over a range of genome sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Our observations also show that the main fraction of dividing cells finish mitosis between 5 and 8 h, the minimum time frame required for cell divisions in plants and other eukaryotes (Mickelson-Young et al., 2016). Therefore, signaling from the wound to initiate cell-cycle transitions in inner adjacent cells must happen very rapidly after tissue disruption and likely relies on non-genomic factors, such as mechanical properties and local geometry of disrupted tissues.…”
Section: Discussionsupporting
confidence: 64%
“…Our observations also show that the main fraction of dividing cells finish mitosis between 5 and 8 h, the minimum time frame required for cell divisions in plants and other eukaryotes (Mickelson-Young et al., 2016). Therefore, signaling from the wound to initiate cell-cycle transitions in inner adjacent cells must happen very rapidly after tissue disruption and likely relies on non-genomic factors, such as mechanical properties and local geometry of disrupted tissues.…”
Section: Discussionsupporting
confidence: 64%
“…Over the 20-min labeling period, EdU uniformly penetrates the root and labels cells in the multiple emerging cell lineages present in the meristematic region ( Figure 1B). Under the same growth conditions, the average length of S phase of mitotic cells in the terminal 1-mm region of the root was estimated to be between 2.7 and 3.9 h (Mickelson-Young et al, 2016). Hence, a 20-min labeling period represents ;10% of the length of S phase.…”
Section: Whole-genome Profiling Of Dna Replication Timing In Maize Romentioning
confidence: 96%
“…The click iT chemistry is nowadays widely used to label replication sites by ethynyl deoxy uridine (EdU). EdU was already successfully applied in Arabidopsis , first to visualize the DNA replication phase in cultured cells ( Kotogany et al, 2010 ; Mickelson-Young et al, 2016 ), and later to track S phase progression in root meristems ( Hayashi et al, 2013 ; Yokoyama et al, 2016 ; Dvorackova et al, 2018 ) or to detect proliferation capacity ( Kazda et al, 2016 ). It was also demonstrated that EdU persists in plant material during growth and that it could be used to track cell fate ( Watson et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%